Identification of missing eastern cultural values during the Covid-19 pandemic in early childhood learning - Joko Pamungkas (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The purpose of this study was to identify Eastern Cultural Values Lost During the Covid-19 Period in Early Childhood Learning. The research method used is a survey. The subject of this research is a kindergarten institution. The data collection technique uses a questionnaire containing what values have been lost during this pandemic. The results of this study are that this pandemic has an impact on the education sector. Learning that used to be face-to-face is now online learning. This has an impact on the loss of missing eastern cultural values, including shaking hands, sitting side by side, recreation together, holding hands, kissing hands, embracing, performing arts, ceremonies, eating together, extra art learning, field trips, gymnastics together, smiling. who bloomed, and in uniform.